2004
DOI: 10.1074/jbc.m308633200
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide 3-Deoxy-d-manno-octulosonic Acid (Kdo) Core Determines Bacterial Association of Secreted Toxins

Abstract: In contrast to cholera toxin (CT), which is secreted solubly by Vibrio cholerae across the outer membrane, heat-labile enterotoxin (LT) is retained on the surface of enterotoxigenic Escherichia coli (ETEC) via an interaction with lipopolysaccharide (LPS). We examined the nature of the association between LT and LPS. Soluble LT binds to the surface of LPS deep-rough biosynthesis mutants but not to lipid A, indicating that only the Kdo (3-deoxy-D-manno-octulosonic acid) core is required for binding. Although cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 56 publications
3
62
0
Order By: Relevance
“…Recently, it has been reported that Kdo2-lipid A also possesses binding affinity to Ctxb to form a complex with LOS via a GM1-independent binding region [44]. The authors demonstrated that the phosphate group on the Kdo core of LOS from Vibrio cholerae as preventing Ctxb from binding to the LOS, resulting in the secretion of soluble toxin across the outer membrane.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, it has been reported that Kdo2-lipid A also possesses binding affinity to Ctxb to form a complex with LOS via a GM1-independent binding region [44]. The authors demonstrated that the phosphate group on the Kdo core of LOS from Vibrio cholerae as preventing Ctxb from binding to the LOS, resulting in the secretion of soluble toxin across the outer membrane.…”
Section: Discussionmentioning
confidence: 92%
“…2). The minimal structure recognized by LT is the Kdo (3-deoxy-Dmanno-octulosonic acid) portion of LPS, and intriguingly, phosphorylation of Kdo inhibits binding by LT as well as its close homolog, cholera toxin (CT) (Horstman et al 2004). The difference in soluble secretion of CT by V. cholerae, compared with the vesicle-associated secretion of LT by ETEC, is therefore explained by the expression of phosphorylated Kdo on the LPS of V. cholerae.…”
Section: Toxin Transportersmentioning
confidence: 99%
“…6 LT toxins are AB 5 toxins (one A subunit linked to a pentameric B subunit) and are transported across the bacterial outer membrane by the type 2 secretion system. 42 LT remains membrane-associated by binding lipopolysaccharide (LPS) 43 and is secreted in outer membrane vesicles (OMVs) that bind to ganglioside receptors on the mammalian cell (GM1a for LT-I or GD1 a/b for LT-II) via the LT-B subunit. The OMVs are then actively endocytosed and the LT transported via the Golgi and endoplasmic reticulum (ER) to the cytosol 44 where the A1 subunit then ADP-ribosylates mammalian guanine nucleotide binding protein a-subunit (G sa ).…”
Section: Molecular Mechanisms Of Virulencementioning
confidence: 99%